Pengaruh Cyberloafing, Stres Kerja, dan Kompensasi terhadap Kinerja Karyawan pada PT. Putra Srikaton Logistics Semarang - Erlian, Fanny Putri (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This study aims to examine the effect of cyberloafing, work stress, and compensation on employee performance at PT. Putra Srikaton Logistics Semarang. Data was collected from respondents in the form of employee data of PT. Putra Srikaton Logistics Semarang. This study used a saturated sample of 110 respondents. The data analysis approach applied is a validity test, reliability test, multiple linear regression test, coefficient of determination test, F test, and t-test in the SPSS version 23 application. The results showed that cyberloafing and work stress have a negative and significant effect on employee performance. While compensation has a positive and significant effect on employee performance.